Pediatricians’ experiences of managing outpatient care during the COVID-19 pandemic: A qualitative study in Germany - von Sommoggy, Julia; Grepmeier, Eva-Maria; Apfelbacher, Christian; Brandstetter, Susanne; Curbach, Janina (Frontiers in Pediatrics, 2023)
Background: Pediatricians are important sources of information for parents regarding their children’s health. During the COVID-19 pandemic, pediatricians faced a variety of challenges regarding information uptake and transfer to patients, practice organization and consultations for families. This qualitative study aimed at shedding light on German pediatricians’ experiences of providing outpatient care during the first year of the pandemic. Methods: We conducted 19 semi-structured, in-depth interviews with pediatricians in Germany from July 2020 to February 2021. All interviews were audio recorded, transcribed, pseudonymized, coded, and subjected to content analysis. Results: Pediatricians felt able to keep up to date regarding COVID-19 regulations. However, staying informed was time consuming and onerous. Informing the patients was perceived as strenuous, especially when political decisions had not been officially communicated to pediatricians or if the recommendations were not supported by the professional judgment of the interviewees. Some felt that they were not taken seriously or adequately involved in political decisions. Parents were reported to consider pediatric practices as sources of information also for non-medical inquiries. Answering these questions was time consuming for the practice personnel and involved non-billable hours. Practices had to adapt their set-up and organization immediately to the new circumstances of the pandemic, which proved costly and laborious as well. Some changes in the organization of routine care, such as the separation of appointments for patients with acute infection from preventive appointments, were perceived as positive and effective by some study participants. Telephone and online consultations were established at the beginning of the pandemic and considered helpful for some situations, whereas for others these methods were deemed insufficient (e.g. for examinations of sick children). All pediatricians reported reduced utilization mainly due to a decline in acute infections. However, preventive medical check-ups and immunization appointments were reported to be mostly attended. Conclusion: Positive experiences of reorganizing pediatric practice should be disseminated as “best practices” in order to improve future pediatric health services. Further research could show how some of these positive experiences in reorganizing care during the pandemic are to be maintained by pediatricians in the future.